Drivers of the Australian native pet trade: The role of species traits, socioeconomic attributes and regulatory systems. Issue 5 (24th February 2022) - Toomes, Adam; García‐Díaz, Pablo; Stringham, Oliver C.; Ross, Joshua V.; Mitchell, Lewis; Cassey, Phillip
Abstract: The pet trade is a major driver of both biodiversity loss and the introduction of invasive alien species. Building a comprehensive understanding of the pet trade would improve prediction of conservation and biosecurity threats, with the aim to prevent further negative impacts. We used South Australia's native wildlife permit reporting system as a data‐rich example of a vertebrate pet market, spanning 590 distinct taxa across 105 families of terrestrial vertebrates (mammals, reptiles, birds and amphibians). Using a piecewise structural equation modelling (SEM) approach, we tested the influence of 11 a priori variables relating to pets (e.g. species traits), pet owners (e.g. socioeconomic metrics) and regulatory systems (e.g. permit requirements) on the quantities of captive pet keeping, breeding, trading and escapes into the wild. Birds and reptiles with higher annual fecundity were more likely to be kept in captivity and birds with larger adult mass were more likely to be sold. Species with more stringent permit requirements were possessed and escaped, in lower abundances. Pet keeping was weakly correlated with regions of lower human population densities and higher unemployment rates, yet all socioeconomic variables were ultimately poor at explaining trade dynamics. More escapes occurred in regions that possessed larger quantities of pets, further emphasising the role of propagule pressure in the risk of pet escapes. Synthesis and applications . Species traits are a strong determinant of native pet trade dynamics, yet permit systems also play a key role in de‐incentivising undesirable trade practices. While our research highlighted the positive potential of trade regulatory systems, we recommend that consistent permit category criteria are established to reduce trade in threatened species as well as invasive alien species of high biosecurity risk. Implementation of such systems is broadly needed across a greater diversity of wildlife markets and jurisdictions. Abstract : Species traits are a strong determinant of native pet trade dynamics, yet permit systems also play a key role in de‐incentivising undesirable trade practices. While our research highlighted the positive potential of trade regulatory systems, we recommend that consistent permit category criteria are established to reduce trade in threatened species as well as invasive alien species of high biosecurity risk. Implementation of such systems is broadly needed across a greater diversity of wildlife markets and jurisdictions.